Increasing Farmer Income By Improved Pig Management Systems - Agustina, Kadek Karang; Wirata, I Wayan; Dharmayudha, Anak Agung Gde Oka; Kardena, I Made; Dharmawan, Nyoman Sadra (Buletin Veteriner Udayana, 2016)
This research aims were to increase house hold income of pig farmer by reconstructing of the pig management systems. The methods used in this study were the application of the problem solving techniques through IPTEKDALIPI programs. The captured data were all expenses incurred and income received in one pig production period before and after intervention. The results showed that there was a significant increase in the income of the farmer from 31.4% to 38.77%. It could be concluded that the pig farmer’s income can be increased through improved management of pig farming systems.
Keywords: pig; income; management; babi; pendapatan; manajemen